BASIC PARAMETERS OF THERMOELECTRIC MATERIALS (Лучшие интеллектуальные исследования, 2025)
Abstract: Thermoelectric materials have gained significant attention due to their ability to directly convert heat into electrical energy and vice versa. The performance of these materials is primarily determined by three key parameters: the Seebeck coefficient (S), electrical conductivity (σ), and thermal conductivity (κ). The interplay among these parameters defines the dimensionless figure of merit, ZT = S²σT/κ, which serves as a standard metric for evaluating thermoelectric efficiency. Optimizing ZT requires balancing high electrical conductivity and Seebeck coefficient with low thermal conductivity. Advanced strategies such as doping, band structure engineering, and nanostructuring have been developed to enhance carrier mobility and suppress phonon transport. Materials like PbTe, SiGe alloys, and Bi-Te based compounds have demonstrated excellent thermoelectric performance, particularly at medium to high temperatures. Anisotropic crystal structures and tailored microstructures also contribute significantly to improved energy conversion. This study reviews the physical and structural factors that influence thermoelectric properties, and highlights the potential of thermoelectric materials for applications in energy harvesting, space exploration, and electronic cooling systems.